Dichloridobis(4-methylbenzyl)(1,10-phenanthroline-kappa N-2,N `)tin(IV) - Keng, T.C.; Lo, K.M.; Ng, S.W. (International Union of Crystallography, 2010)
The tin(IV) atom in the title compound, [Sn(C8H9)(2)Cl-2(C12H8N2)], is chelated by the N-heterocycle and bonded to two C atoms and two chloride ions in an SnC2Cl2N2 octahedral coordination environment with the C atoms trans to each other. The dihedral angles between the heterocycle ring system and the benzene rings of the 4-methylbenzyl groups are 21.20 (12) and 28.71 (11)degrees.